Achieving a systematic service integration program for children with challenging behaviors in school setting in Lebanon. (c2015) - Mahmoud, Hadeel (2016)
Students with behavioral problems display deficits in social skills, such as deficits initiating social interactions, lack of orientation towards a stimulus, and other social issues. Research showed that school based interventions aim at reducing disruptive behaviors, thus implementing school based interventions are of high importance. This study aims at implementing a social skills based program/intervention on a child with behavioral problems. Another purpose is to evaluate the efficacy of social skills training (SST) with a student with a behavioral problem. This case study took place at a school located in Mount Lebanon area. The results show that school-based interventions serve as a crucial factor in the treatment plan of the student. Another finding is that the disruptive behavior displayed by the student decreased throughout the intervention period. Future research requires more attention to school based interventions and social skills programs. However, there are limitations of this study, which need to be taken in consideration for further studies.